Regulating the Legal Quagmire of Artificial Intelligence and Copyright Infringement in Cameroon and Across Africa - Nyadjroh Gabsa, Lidwina (Revue Internationale de Droit et Science Politique, 2025)
The rapid advancement of artificial intelligence (AI) technologies presents unprecedented prospects and plight within the realm of copyright law. This article investigates the strained interplay between AI-generated content and copyright infringement in Cameroon and across Africa, where legal frameworks often lag behind technological innovations. The concern arises from the ambiguity surrounding authorship, ownership, and the applicability of existing copyright laws to AI-generated works, which poses significant risks for creators and innovators. The question on how does current copyright legislation in Cameroon and broader African jurisdictions address the challenges posed by AI is the core of this work. Legal gaps exist, thereby creating the need to address the constrains introduced by AI, necessitating a reevaluation and reform of copyright laws. Employing a doctrinal and extensive online search, findings of this work reveal that many African nations, including Cameroon, a member of OAPI, lack specific regulations addressing AI's implications for copyright, resulting in uncertainty for creators. The results show a pressing need for revisiting of copyright laws in Cameroon and across Africa, to ensure robust protection for AI-generated works while promoting technological advancement. This article recommends adapting copyright laws for AI-generated works, the need for regional cooperation to explicitly adopt standard definitions of AI and AI operations to circumvent infringement claims, and also incorporate a unified approach to resolve the debate on copyright protection on AI status recognition of authorship and ownership, to enhance legal certainty, creativity and innovation. Le développement rapide des technologies d'intelligence artificielle (IA) ouvre des perspectives inédites, mais soulève également des défis majeurs en matière de droit d'auteur. Cet article examine les interactions complexes entre les contenus générés par l'IA et la contrefaçon au Cameroun et en Afrique, où les cadres juridiques sont souvent en retard sur les innovations technologiques. L'ambiguïté entourant la paternité, la propriété et l'applicabilité du droit d'auteur aux œuvres générées par l'IA est source d'inquiétude, car elle représente un risque important pour les créateurs et les innovateurs. La question de savoir comment la législation actuelle sur le droit d'auteur au Cameroun et, plus largement, dans les juridictions africaines, appréhende les défis posés par l'IA est au cœur de cette étude. Des lacunes juridiques existent, d'où la nécessité de remédier aux contraintes introduites par l'IA et, par conséquent, de réévaluer et de réformer le droit d'auteur. S’appuyant sur une recherche doctrinale et en ligne exhaustive, cette étude révèle que de nombreux pays africains, dont le Cameroun, membre de l’OAPI, ne disposent pas de réglementations spécifiques concernant les implications de l’IA en matière de droit d’auteur, ce qui engendre une incertitude pour les créateurs. Les résultats soulignent l’urgence de revoir les lois sur le droit d’auteur au Cameroun et dans toute l’Afrique, afin de garantir une protection solide des œuvres générées par l’IA tout en favorisant le progrès technologique. Cet article recommande d’adapter les lois sur le droit d’auteur aux œuvres générées par l’IA, de renforcer la coopération régionale pour adopter explicitement des définitions standardisées de l’IA et de ses opérations afin de prévenir les actions en contrefaçon, et d’intégrer une approche unifiée pour résoudre le débat sur la protection du droit d’auteur concernant le statut de l’IA, la reconnaissance de la paternité et de la propriété intellectuelle, afin d’améliorer la sécurité juridique, la créativité et l’innovation.
Keywords: AI; Contrefaçon; Copyright; Droit d'auteur; IA; Impasse juridique; Infringement; Intellectual property; Legal Quagmire; Propriété intellectuelle; Regulation; Réglementation

Le consentement en droit de la propriété littéraire et artistique - Dramé, Mamadouba (Université de Lorraine, 2025)
Le processus d'autonomisation du droit de la propriété intellectuelle par rapport au droit commun en France a atteint son apogée à travers la loi n° 92-597 du 1re juillet 1992 qui créa un code en la matière. Depuis cette date, la matière n'a cessé de se développer. Et cette évolution n'est pas sans conséquence sur le consentement des différents acteurs du secteur. Il est question du consentement à tous les niveaux : que ce soit sur les opérations juridiques (cession, licence, contrat d'édition etc.) dont les œuvres font objet ou encore sur la volonté affichée par le législateur de protéger l'auteur ou le créateur de toute œuvre de l'esprit. L'objectif de cette thèse est donc de démontrer les manifestations du consentement de l'auteur ainsi sa particularité par rapport au droit commun. The process of making intellectual property law autonomous from common law in France reached its apogee with Law no. 92-597 of July 1, 1992, which created a code on the subject. Since then, the field has gone from strength to strength. And this evolution is not without consequences for the consent of the various players in the sector. Consent is an issue at every level, from the legal transactions (assignment, licensing, publishing contracts, etc.) to which works are subject, to the legislator's desire to protect the author or creator of any work of the mind. The aim of this thesis is therefore to demonstrate the manifestations of the author's consent, and how it differs from common law.
Keywords: Artificial Intelligence; Consent; Consentement (droit); Contract; Contrat; Contrefaçon; Copyright; Copyright infringement; Droit d'auteur; Exceptions aux droits d'auteur; Exceptions to Copyright; Intellectual property; Intelligence artificielle; Propriedade intelectual; Propriété intellectuelle

An Assessment of Concurrent Jurisdiction and Claim of Ownership of Trademarks under OAPI Legislation - Dashaco Akuriah, Nelson (International Multilingual Journal of Science and Technology, 2025)
Trademarks are economic tools that aid businesses to communicate with their customers and capture a vast section of the population. Trademarks are only useful when used efficiently in the course of trade, meaning the higher the reputation of the mark, the more consumers want to associate themselves to the products or services the mark is affixed upon. This study examines the criteria to own a trademark and how ownership claims are handled between the African Organisation of Intellectual property as known by its French acronym OAPI and the competent domestic courts found at the level of Member States which has become a breathing ground for confusion in the resolution of disputes. Due to both bodies having concurrent jurisdiction in dispute resolution, the cost has become unbearable on trademark owners or beneficiaries of an exclusive license of exploitation, coupled with inconsistency in judgements from the two structures. The article highlights some key improvements expanding trademark subject matter and provides information on how the two institutions cited above handle matters of jurisdiction based on case law. The article also brings to the limelight how the OAPI administrative litigation bodies can collaborate with the competent domestic courts to arrive at clear and concise decisions. In conclusion the paper provides some recommendations on bridging the gap between both jurisdictions in order to attain the objectives of all parties involved.
Keywords: Concurrent Jurisdiction; Intellectual property; Litigation; Ownership; Registration; Trademarks; Use

Le potentiel de la propriété intellectuelle pour le développement en Afrique : le cas du droit des marques dans les pays membres de l'OAPI - Massala, Kélicia (Université de Montréal, 2025)
Ce mémoire explore le potentiel du droit des marques comme levier stratégique de développement socio-économique dans les États membres de l’OAPI. En s’appuyant sur une analyse rigoureuse du système juridique harmonisé issu de l’Accord de Bangui, il met en lumière les forces et les limites du cadre actuel, à l’aune des défis structurels, institutionnels et économiques qui caractérisent la région. À travers une approche multidisciplinaire, combinant analyse doctrinale, données empiriques et entretiens de terrain, ce travail examine les mécanismes concrets de valorisation des marques locales, les disparités entre titulaires nationaux et étrangers, ainsi que les stratégies d’accompagnement en matière de sensibilisation, de formation et d’accès au système. Il propose également des pistes de réforme et des recommandations pour renforcer l’écosystème de la propriété intellectuelle au service de l’innovation, de la compétitivité des PME et de la protection des savoirs locaux. En filigrane, ce mémoire interroge la capacité des droits de propriété intellectuelle à contribuer de manière durable à l’émergence économique du continent africain.
Keywords: Développement économique; Economic Development; Innovation; Intellectual property; Legal Reforms; Marques; OAPI; PME; Propriedade intelectual; Propriété intellectuelle; Réformes juridiques; SMEs; Trademarks; Valorisation des savoirs locaux; Valorization of Local Knowledge

L’œuvre libre : essai d'analyse contractuelle - Chevallier, Adélaïde (Université de Bordeaux, 2025)
L’oeuvre libre, aussi connue sous le nom d’open source, est une création protégée par le droit d’auteur, mais dont l’exploitation est ouverte à tous. Si l’expression reste à ce jour peu connue du grand public, les oeuvres libres sont désormais un incontournable des pratiques quotidiennes, en attestent le succès de l’encyclopédie en ligne Wikipédia et l’attrait croissant pour les logiciels libres tels Linux, OpenOffice ou la plateforme Moodle. Malgré son essor, le phénomène du libre demeure juridiquement peu, voire mal, appréhendé. De surcroît, sa licéité fait régulièrement l’objet de contestations doctrinales, l’oeuvre libre s’inscrivant à rebours des règles traditionnelles du droit français, selon lesquelles les biens sont intangibles, non numériques et réservés à l’usage exclusif de leur titulaire. La finalité de l’étude consiste dès lors à démontrer qu’en dépit de son caractère disruptif, l’oeuvre libre peut en l’état intégrer l’ordre juridique français au moyen d’une analyse contractuelle. The concept of the “free cultural work,” also referred to as open source, designates a creation protected by copyright yet made available for use by all. While the expression remains relatively unfamiliar to the general public, free cultural works have become indispensable in contemporary practice, as illustrated by the success of the online encyclopedia Wikipedia and the growing appeal of free software such as Linux, OpenOffice, and the Moodle platform. Notwithstanding this expansion, the legal phenomenon of free cultural works continues to be only partially, if not inadequately, addressed. Furthermore, its legitimacy is the subject of recurrent doctrinal debate, insofar as the free cultural work stands in contrast to the traditional principles of French law, according to which property is tangible, non-digital, and reserved for the exclusive use of its owner. The purpose of this study is therefore to demonstrate that, despite its disruptive character, the free cultural work may, in its current form, be accommodated within the French legal order through contractual analysis.
Keywords: Contract law; Contrat; Copyright; Droit d'auteur; Free cultural works; Free license; Free software; Intellectual property; Licence libre; Logiciel libre; Oeuvre libre; Open source; Propriété intellectuelle

Fairness, Digital Markets and Competition Law – Reconciling Fairness Norms in Digital Markets Act, Data Act and AI Act with Competition Law - Kianzad, Behrang (Journal of Law, Market & Innovation, 2025)
The present article explores the implication of fairness as a regulatory and competition law concept applied to digital and Artificial Intelligence markets, in light of recent law and policy developments targeting the interaction between data, market power and competition law. Much of the policy discussions, legislative proposals as well some emerging case law elevate the matter of “fairness” in the context of digital markets and AI, creating both a novel regulatory framework as well as encouraging competition law to curb “unfairness” of said markets and related “unfair practices”. The interface between intellectual property rights and competition law is of utmost importance in this context, where we might find similar analogous insights as we can find regarding the matter of fairness within traditional EU competition law. Further, the question remains whether the “fairness norm” expressed in regulatory acts such Digital Markets Act, EU AI Act and the EU Data Act are akin to the “fairness” norms found in Union competition law, mainly under Article 102 Treaty on the Functioning of the European Union (TFEU).

Contribution à l’étude de la réservation des utilités des données numériques - Grave-Renaud, Gonzague (Université de Lille, 2025)
La dématérialisation et la numérisation croissantes de notre économie ont élevé les données au rang de matière première indispensable. La valeur des données réside dans leurs exploitations potentielles. C’est pourquoi leurs détenteurs cherchent à maximiser leurs revenus en limitant l’accès. Ce constat souligne les enjeux de gouvernance des données. La problématique de la réservation des données a alors émergé. Le constat est que la propriété intellectuelle ne parvient pas à appréhender pleinement la donnée. Néanmoins, l’analyse du droit positif révèle l’existence de mécanismes du droit commun permettant une réservation des utilités des données, tels que le contrat, la concurrence déloyale et parasitaire et le secret des affaires. Bien que ces mécanismes offrent une réservation, ils ne sont pas exempts de lacunes. Aussi, la question de la propriété des données a émergé et a suscité un vif débat. Cette interrogation a engendré un renouvellement des approches théoriques et pratiques du droit de propriété. Dans une approche prospective, un droit exclusif d’exploitation sur les données a été esquissé sous la forme d’un droit sui generis. Cet exercice de conceptualisation a mis en exergue les difficultés que pourrait entraîner une telle reconnaissance. Par ailleurs, il est impératif de trouver un juste équilibre entre la volonté d’appropriation des données et le droit d’accès des tiers à celles-ci afin d’instaurer un régime de protection à la fois efficace et équitable.
Keywords: Biens incorporels; Brevets d'invention; Contrats; Data; Données; Droit d'auteur; Droit des affaires; Droit d’accès; Intellectual property; Investissements; Investments; Propriedade intelectual; Propriété; Propriété intellectuelle; Protection de l'information (informatique) – Droit; Reservation; Responsabilité (droit); Right of access; Réservation; Secret; Systèmes d'information; Valeur; Value

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy